The correlation between bullying behavior and students’ self-confidence levels at MTs Labanan Makmur - Arifin Siregar; Rahmad Hakim (Educenter : Jurnal Ilmiah Pendidikan, 2025)
Bullying incidents in school settings still occur frequently and are feared to have serious impacts on students’ development. This study aims to analyze the correlation between bullying behavior and students’ self-confidence at MTs Labanan Makmur. This study employed a quantitative approach, involving a sample of 33 seventh-grade A students from a total population of 167. The sample was selected using Arikunto’s conditional sampling technique. Data were collected by distributing a questionnaire consisting of 20 statements to the entire sample, and the data were analyzed using the product-moment (Pearson) correlation technique. The findings indicate that the majority of students have high levels of self-confidence, even though bullying behavior remains relatively high. This finding is supported by the results of the product-moment correlation analysis, which yielded a value of r = -0.10, indicating a negative relationship with a very low correlation coefficient between bullying and students’ self-confidence. Thus, this study confirms the existence of a very weak negative relationship between bullying behavior and students’ self-confidence. Therefore, the roles of teachers and parents are crucial factors in efforts to prevent bullying and enhance students’ self-confidence.